O papel da assistência técnica e extensão rural na evolução dos agroecossistemas familiares, fundamentados por práticas agroecológicas na microrregião de Pato Branco – PR - Bortolotti, Mônica Aparecida (2014)
The main purpose of this research was to evaluate the evolution of family agroecosystems supported by agroecological practices in the microregion of Pato Branco – PR, and the role developed by technical assistance and rural extension in this process. The theoretical foundation consists of sustainable development concepts and rural sustainable development in agroecosystems, technical assistances and rural extension in the evolutionary and historical context. The procedure, concerning the objectives, consists in a descriptive research, concerning the methods, consists in a bibliographical and desk research and a survey based on interviews with five farmers, one representative of Verê’s CAPA and two Francisco Beltrão’s ASSESOAR representatives. Main results: The historical context of agroecosystems, although having similar characteristics – all develop horticulture and they are farmers with family farming characterization - currently present in different social, economical and organizational context. The agroecosystem “A”, sustained continuously with Technical Assistance and Rural Extension (TARE) from NGOs exclusively, often accessing the TARE policies, the most recent being the Pronaf Mais Alimentos; Agroecosystem “B”, assisted with private and NGOs TARE, but not continuously, joined also the Field Housing Plan, building a new residence recently. Agroecosystem “C” reported that they received guidance of private and NGOs TARE, also not continuously, currently they don’t develop the production of organic vegetables anymore and never searched for TARE Public policy. Agroecosystem “D” reported that they received orientation from the University, City Hall representatives, Certification Institutes and NGOs, until now they do not have organic production certification and just recently applied one of the TARE policy, Pronaf Mais Alimentos. Finally, agroecosystem “E” receives TARE from SEBRAE and Certification Institutes, also NGOs, currently used the Pronaf Mais Alimentos. Therefore, it is possible to establish the use of TARE policies in the agroecosystems surveyed, then, new studies are needed to verify the efficiency in TARE application to the future of these agroecosystems.